A longitudinal analysis for informativeness of earnings announcements in Borsa Istanbul. Issue 2 (5th November 2019) - Ahlatcioglu, Aykut; Okay, Nesrin
Abstract : Purpose: The purpose of this paper is to assess the information value of earnings announcements for the 2007–2017 period in Borsa Istanbul. Design/methodology/approach: Abnormal volatility (AVOL) and abnormal absolute return (AAR) in the three-day window around the earnings announcement are used as proxies for information content. A pooled regression of AVOL and AAR is conducted to test for the existence of information content and analyze its time trend along with its determinants. Findings: The authors find significantly positive AVOL and AAR which shows that earnings have information content for investors during the sample period. Furthermore, both proxies demonstrate a positive time trend after controlling for various firm characteristics and surprise measures. The authors take this as evidence that overall informativeness of earnings has increased over time. The authors observe that this increase is most prevalent for growth companies and earnings announcements with high absolute surprise. This study provides partial support for the hypothesis that value of earnings announcements has increased after an improvement in information dissemination technology with the inception of the online disclosure platform, KAP. Practical implications: Understanding information value of earnings announcements is of interest for companies which prepare earnings reports, regulators who set standards on their content and frequency and investors which make investment decisions based on information released at these announcements. Originality/value: There had been few non-US studies related to information value of earnings announcements. The overwhelming majority of these are conducted using limited data sets from the latter part of the last century and only analyze annual earnings announcements. The authors aim to shed light on the subject using a broad and recent sample of quarterly earnings announcements from a major emerging market, Turkey.